Endoscopic mucosal resection of large rectal adenomas in the era of centralization: Results of a multicenter collaboration. Issue 6 (1st December 2014) - Barendse, RM; Musters, GD; Fockens, P; Bemelman, WA; de Graaf, EJ; van den Broek, FJ; van der Linde, K; Schwartz, MP; Houben, MH; van Milligen de Wit, AW; Witteman, BJ; Winograd, R; et al.
Abstract : Background and objective: Endoscopic mucosal resection (EMR) of large rectal adenomas is largely being centralized. We assessed the safety and effectiveness of EMR in the rectum in a collaboration of 15 Dutch hospitals. Methods: Prospective, observational study of patients with rectal adenomas >3 cm, resected by piecemeal EMR. Endoscopic treatment of adenoma remnants at 3 months was considered part of the intervention strategy. Outcomes included recurrence after 6, 12 and 24 months and morbidity. Results: Sixty‐four patients (50% male, age 69 ± 11, 96% ASA 1/2) presented with 65 adenomas (diameter 46 ± 17 mm, distance ab ano 4.5 cm (IQR 1–8), 6% recurrent lesion). Sixty‐two procedures (97%) were technically successful. Histopathology revealed invasive carcinoma in three patients (5%), who were excluded from effectiveness analyses. At 3 months' follow‐up, 10 patients showed adenoma remnants. Recurrence was diagnosed in 16 patients during follow‐up (recurrence rate 25%). Fifteen of 64 patients (23%) experienced 17 postprocedural complications. Conclusion: In a multicenter collaboration, EMR was feasible in 97% of patients. Recurrence and postprocedural morbidity rates were 25% and 23%. Our results demonstrate the outcomes of EMR in the absence of tertiary referral centers.